Modelo para medir los beneficios de una arquitectura empresarial (2015)
"Business architectures began their peak in the late 80s, since then there has been much talk about the subject and different methodologies have emerged to develop a business architecture such as TOGAF, Zachman, DODAF, but they all have something in common: Technology at the service of the business. For a long time people who were accustomed to perform all their activities with paper, pencil, typewriter, calculators, among others. When they started using software, they were reluctant to believe in the power of computers and to understand that something so small involved complex activities. Part of this resistance was the result of bad experiences with information systems, sometimes you hear comments like: "It was better my paper and pencil", "I did not trust that system" "The system is useless". With the business architecture, it is sought that the technology really helps to meet the objectives of the organization. When you hear about the business architecture, it seems a very effective solution for companies to work with technology efficiently, but the contribution does not come only to that point, it is transversal to the entire organization. A good business architecture exercise should consider business, information, information systems and technology as a whole ... "- Extract from the document